Higher Gene Expression of Healing Factors in Anterior Cruciate Ligament Remnant in Acute Anterior Cruciate Ligament Tear. Issue 7 (June 2018) - Novaretti, João Victor; Astur, Diego Costa; Casadio, Davi; Nicolini, Alexandre Pedro; de Castro Pochini, Alberto; Andreoli, Carlos Vicente; Ejnisman, Benno; Cohen, Moises
Background: Anterior cruciate ligament (ACL) reconstruction with remnant preservation has been described and related to potential advantages. Literature is lacking regarding gene expression of potential factors related to ligament healing in the ACL remnant and its relation to time from injury. Hypothesis: The mRNA expression of ligament healing factors in the ACL remnant would be higher in acute tears (<3 months from injury) than in intermediate (3-12 months) and chronic (>12 months) injuries. Study Design: Controlled laboratory study. Methods: Gene expression of 21 genes related to ligament healing factors was analyzed in 46 ACL remnants biopsied during surgical reconstruction with quantitative real-time polymerase chain reaction technique. Specimens were divided into 3 groups according to time from injury: acute (<3 months from injury; n = 19), intermediate (3-12 months; n = 12), and chronic (>12 months; n = 15). Histological and immunohistochemical evaluation was performed by analysis of hematoxylin and eosin, CD-34, and S-100 staining. Results: Expression of COL1A1, COL1A2, COL3A1, COL5A1, COL5A2, COL12A1, LOX, PLOD1, and TNC genes in ACL remnant was greater in acute compared with chronic injuries. COL1A1, COL5A1, COL12A1, and TNC genes were also expressed more in the acute group compared with the intermediate group. Furthermore, expression of the genes COL1A1 and COL5A2 was significantly higher in female than in male patients. No difference in the number of blood vessels and mechanoreceptors among groups was observed in the microscopic evaluation. Conclusion: The present study demonstrates that expression of COL1A1, COL1A2, COL3A1, COL5A1, COL5A2, COL12A1, LOX, PLOD1, and TNC genes in ACL remnant is greater in acute (<3 months from injury) compared with chronic (>12 months) injuries. Furthermore, COL1A1, COL5A1, COL12A1, and TNC genes were expressed more in the acute group compared with the intermediate group (3-12 months from injury). Clinical Relevance: ACL reconstructions with remnant preservation should be performed in patients with acute injuries, as in these cases the ACL remnant may present the greatest healing potential.